Gestão do conhecimento aplicada a comunidades produtivas artesanais - Wanderley, Renata Garcia [UNESP] (2015)
In contemporary times, handicraft is still an active agente and a significant representative of the Brazilian economy, society and even politics, especially from the Northeast region. This research conceptualizes it with three required qualities: 1) predominance of handwork, 2) craftsmen identify and signature and 3) social and cultural values. Even knowing its importance, this research, based on field research by observation, presents a problematic context of handicraft work. As a solution to this problem, some intervention of design programs are structured and several actions are developed at productive handicraft communities. Four of these programs were used as references for this research: 1) Programa de Artesanato Brasileiro; 2) Artesol; 3) Programa SEBRAE de Artesanato; e 4) O imaginário. In addition, some agents of these programs were interviewed and it was possible to identify some difficulties and problems that the workers have. To attend the handicraft needs and remediation of the issues of handicraft activities and the intervention programs, this research has built a Shared Design. This is qualified as a model program to an intervention of design and handicraft, more direclty to identify, share and integrate their knowledge to build a knowledge network (knowledge management)